Immunotherapy for extensive-stage small-cell lung cancer: current landscape and future perspectives - Zhang, Shuang; Cheng, Ying (Frontiers in Oncology, 2023)
Small-cell lung cancer (SCLC) is a fatal subtype of lung cancer characterized by high aggressive-ness, poor prognosis, and limited treatment options. For the first time in more than three decades, it has been demonstrated that the addition of immunotherapy to chemotherapy improved the survival of patients with extensive-stage SCLC, thereby establishing a new standard of first-line treatment. However, it is important to improve the curative effect of immunotherapy on SCLC and identify the patients who could benefit the most from such treatment. In this article, we re-view the current data, the development of novel immunotherapy strategies, and the discovery of potential predictive biomarkers of immunotherapy for SCLC.